Language Anxiety in Speaking Skills among the Students of Arabic Language Teaching Department at the State Islamic Institute of Lhokseumawe: القلق اللغوي في مهارة الكلام لدى طلبة قسم تدريس اللغة العربية بالجامعة الإسلامية الحكومية لهؤسماوى - Teriza, Rana; Kurniawan, Edo (Al Mihwar: Jurnal Pendidikan Bahasa Arab dan Kebahasaan, 2024)
Language anxiety is a significant challenge that students encounter when speaking a foreign language. It encompasses self-perceptions, emotions, and behaviors related to learning in language classes, often manifesting as negative thoughts, fear of failure, and nervousness. This anxiety can hinder students' speaking abilities. Therefore, this study aims to identify the factors contributing to language anxiety and assess its level in students’ speaking skills using the Horwitz Foreign Language Anxiety Scale (FLCAS). The research employs a quantitative survey method. The study population consists of 146 students from the Arabic Language Education Department for the academic year 2023-2024, with a sample of 60 students selected through incidental sampling. Data were collected using questionnaires. The findings reveal that language anxiety among students stems from three main factors: communicative anxiety due to psychological influences, assessment anxiety influenced by teachers and peers, and test anxiety triggered by situational factors. The overall level of language anxiety among students in the Arabic Language Education Department at Lhokseumawe State Islamic Institute averages 31, or 51.67%. This suggests that while students are aware of the causes of their anxiety, they still make an effort to speak. The results indicate a strong determination among students to overcome their language anxiety and continue practicing Arabic despite their struggles. However, there is no correlation between the questionnaire scores and the students' muhadatsah (speaking) lesson scores. The findings imply that reducing language anxiety through supportive teaching can enhance students’ confidence in speaking Arabic.